ETNOMEDISIN SEBAGAI SOLUSI ALTERNATIF PADA PERMASALAHAN EKONOMI DAN KESEHATAN MASYARAKAT DI DESA BAGAN KECAMATAN PERCUT SEI TUAN, KABUPATEN DELI SERDANG - Puspitawati, Puspitawati; Ekomila, Sulian; Hasanah, Noviy (JUPIIS: Jurnal Pendidikan Ilmu-ilmu Sosial, 2013)
Indonesia is a multi-ethnic country consisting of hundreds of tribes and cultures who are faced with various problems including health issues. Health and disease are major problems facing the people of Indonesia since prehistoric times. Similarly, the city of Medan percut sei districts are faced with a host of health and disease. At the community in addressing pain and its treatment often make use of modern medical services when their economic conditions are not sufficient. While they can actually use the land in the yard to grow nutritious crops for the first treatment. Indonesia is also rich in ethnic groups that reached more than 370 ethnic and traditional knowledge which is the nation´s cultural heritage in the use of herbs for health maintenance and treatment of hereditary diseases. In the study of anthropology known as ethnomedicine treatment. It is very interesting when examined from the standpoint of anthropology, especially about the treatment ethnomedicine.